Urban Cepaea nemoralis snails are less likely to have nematodes trapped within their shells - Dahirel, Maxime; Reyné, Hannah; De Wolf, Katrien; Bonte, Dries (Peer Community Journal)

(untitled)
Urbanization is a major human-induced environmental change which can impact not only individual species, but also the way these species interact with each other. As a group, terrestrial molluscs interact frequently with a wide diversity of parasites, yet the way these interactions vary across space and in response to environmental pressures is poorly documented. In this study we leveraged a recently discovered defence mechanism, by which snails trap parasitic nematodes in their shells, to explore how snail-nematodes interactions may vary in response to city life. We examined shells from the generalist snail Cepaea nemoralis sampled in three urban areas in Belgium for trapped nematodes, and attempted to link this to urbanization and shell phenotypic traits. We found that even a small degree of urbanization led to large decreases in the rates of shell encapsulation, and that larger snails were more likely to contain trapped nematodes. However, we found no evidence that shell colour, which had been previously linked to immune function, was correlated to encapsulation rates. We discuss how between-population variation in encapsulation rates can result from urbanization-induced changes on the nematodes side, the snail side, or both, and suggest potential tests for future studies aiming to disentangle these mechanisms.